The 𝑒-positive mild solutions for fractional impulsive evolution equations with 1 < 𝛼 < 2 - Féres Junior, Jorge; Sousa, José Vanterler da Costa; Oliveira, Edmundo Capelas de (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this paper, we investigate the existence of global 𝑒-positive mild solutions for impulsive evolution fractional differential equation in the Caputo sense of order 1 < 𝛼 < 2. To obtain the result, we usually the theory of sectorial operators, theory of Kuratowski measure of noncompactness, Cauchy criterion and the Gronwall inequality.